2014
DOI: 10.1108/imds-04-2013-0171
|View full text |Cite
|
Sign up to set email alerts
|

Co-creating business value of information technology

Abstract: Purpose – IT-based supply chain performance is co-created through inter-organizational business processes. This research is motivated to explore how business value of IT in supply chain is co-created in downstream process and probe into the possible complementary effect of relational resources from retailers and customers during the cooperative process. The paper aims to discuss these issues. Design/methodology/approach – A model is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
(76 reference statements)
0
20
0
1
Order By: Relevance
“…It is emerging research topic in e-commerce and the list of issues related to e-commerce are e-supply chain capability, e-CRM, performance and process of co-creating business value [38].…”
Section: Marketing and Crm Issuementioning
confidence: 99%
“…It is emerging research topic in e-commerce and the list of issues related to e-commerce are e-supply chain capability, e-CRM, performance and process of co-creating business value [38].…”
Section: Marketing and Crm Issuementioning
confidence: 99%
“…Cost Efficiency, Cost Reduction [6], [78], [68], [73], [76], [70], [28] Process Efficiency Production Effectiveness [40], [50], [73], [52], [28] Operasional Efficiency [65], [39] Time Efficiency [71], [45], […”
Section: Eficiency Performance Cost Efficiencymentioning
confidence: 99%
“…Internal Capabilities Managing Internal IT Relationship IT Operations/Use Capability [41], [39], [9], [45] System Integration, Collaboration [55] Data/Information Sharing [52], [50], [76] Technology Sensing & Responding [46], [49] Managing Internal Organization Capability…”
Section: Dimensions Indicators Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, RBV indicates that firms obtain value by developing IT-enabled organizational capabilities to acquire, integrate, and reconfigure IT-related resources that are embedded in the firm's structural, cultural and process contexts [6,43,57]. Both views acknowledge that IT resources may not generate business value directly, but they can enable intermediate transformational processes and generate higher order organizational capabilities that are sources of firm performance [37,57,66]. Although prior research has identified relationships among IT, business process, and performance [2,13,62,75], few studies have examined how to leverage the e-business process to create business value in the information systems and operations management disciplines.…”
Section: Introductionmentioning
confidence: 99%